The Church of the Future: A Model for the Year 2001 - Kulangara, G (Journal of Dharma, 1989)
Walbert Buhlmann, The Church of the Future, A Mode/ for the Year 2001, Orbis Books, Maryknoll, New York, 1986, pp. 16+210. $ 10.95.